Seasonal study on soil salinity and its relation to other properties at Satkhira district in Bangladesh - Kumar, U; Mitra, JR; Mia, MY (Progressive Agriculture, 2019)
The study was conducted at Shyamnagar and Talaupazila of Satkhira district in Bangladesh to know about the soil salinity and its relation to other properties of soil in both dry and wet season and comparison the present status of soil between two upazilas. Electrical Conductivity (EC) value of the study area showed that yield of many crops can be restricted in dry season due to salinity. Mean EC was slightly saline (5.93 dsm-1) in dry season and non- saline (0.61 dsm-1) in wet season. Ranges of pH were slightly acidic to slightly alkaline (6.2 to 7.5) in dry season and slightly acidic to neutral (5.7 to 6.9) in wet season. pH values indicate it was suitable for crop production. Mean Organic Matter (OM) status was low in both seasons (1.5 % in dry season and 1.6 % in wet season). Mean total N status was very low (0.08 %) in dry season and low (0.10 %) in wet season. Mean status of P in the study areas was low (8.08 µgg-1 soil) in dry season and very low (4.98 µgg-1 soil) in wet season. Mean status of K, Ca, Mg, S and Zn were very high in both season of study area and this was may be due to excessive fertilizer use and inherent properties of soil in the agricultural land. Mean status of B was high in Tala in both season and in Shyamnagar was high in dry season and optimum in wet season. To test the significance of the pair of parameters p-value has been measured. Pearson’s correlations among the different parameters were done to identify the highly correlated and interrelated soil quality parameters. EC showed significant and positive correlation with Potassium, Sulphur and Zinc in dry season. Although chemical properties of soil at Shyamnagar and Talaupazila was not found similar and optimum level but it was found that the chemical properties of soil of wet season more suitable than the dry season because of soil salinity. Progressive Agriculture 30 (2): 157-164, 2019